2013
DOI: 10.1088/0004-637x/773/2/115
|View full text |Cite
|
Sign up to set email alerts
|

STUDYING INTERCLUSTER GALAXY FILAMENTS THROUGH STACKING gmBCG GALAXY CLUSTER PAIRS

Abstract: We present a method to study the photometric properties of galaxies in filaments by stacking the galaxy populations between pairs of galaxy clusters. Using Sloan Digital Sky Survey data, this method can detect the inter-cluster filament galaxy overdensity with a significance of ∼ 5σ out to z = 0.40. Using this approach, we study the g − r color and luminosity distribution of filament galaxies as a function of redshift. Consistent with expectation, filament galaxies are bimodal in their color distribution and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…Pimbblet, Drinkwater & Hawkrigg 2004), or by stacking analysis from photometric galaxy surveys (e.g. Zhang et al 2013). While these studies confirm the strategy to focus on cluster pairs, they provide limited information into the nature of cosmic filaments; these luminous systems represent 10 per cent of the baryonic matter, their distribution and motions need not trace the majority of the gas, and they offer no insight into the presence of a WHIM.…”
Section: Introductionmentioning
confidence: 83%
“…Pimbblet, Drinkwater & Hawkrigg 2004), or by stacking analysis from photometric galaxy surveys (e.g. Zhang et al 2013). While these studies confirm the strategy to focus on cluster pairs, they provide limited information into the nature of cosmic filaments; these luminous systems represent 10 per cent of the baryonic matter, their distribution and motions need not trace the majority of the gas, and they offer no insight into the presence of a WHIM.…”
Section: Introductionmentioning
confidence: 83%
“…The photometric properties of the galaxies in the inter-cluster filament, their star-formation evolution, their weak lensing properties, etc. were performed in many selected cluster (or group) pairs (e.g., Fadda et al 2008;Gallazzi et al 2009;Edwards et al 2010;Zhang et al 2013;Martínez et al 2016;Epps & Hudson 2017 A&A proofs: manuscript no. aa_new may show substructures or evidence of dynamical effect: they merge, interact, and accrete smaller groups.…”
Section: Introductionmentioning
confidence: 99%
“…Colberg et al (2005) suggested that the probability of finding a fil-E-mail: julian@oac.unc.edu.ar ament between systems of galaxies is strongly dependent on their separation. Zhang et al (2013) used the SDSS Data Release 8 (Aihara et al 2011) and detected filaments using a sample of more than 50,000 clusters of galaxies. They selected cluster pairs separated by less than 35h −1 Mpc and found that richer clusters are connected to richer filaments.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the filaments in this process has not been extensively studied. Zhang et al (2013) studied the colour and luminosity distribution of galaxies in filaments. They found that filament galaxies are bluer and fainter than cluster members.…”
Section: Introductionmentioning
confidence: 99%